2016
DOI: 10.1590/2179-8087.109714
|View full text |Cite
|
Sign up to set email alerts
|

Some Properties of Astronium graveolens Wood Along the Stem

Abstract: We investigated the axial variation of specific gravity, shear parallel to the grain and anatomical features of Astronium graveolens wood and related these properties to the anatomy along the stem. We felled five 20-year-old trees and cut discs from four different stem heights, including stem base, 1 meter, 2 meters and 3 meters, for a total of 20 discs, and studied wood samples near the bark and at the base of trunk. Axial variations found appear to provide a balance between mechanical strength of the wood at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Many publications describe the various longitudinal variation patterns within trees. The recent work of Kiaei and Farsi (2016) for Persian silk wood (Albizzia julibrissin) illustrated wood density, modulus of elasticity and modulus of rupture in bending decreased from base to top with height, and Longui et al (2016) for Astronium graveolens showed specific gravity was higher at the base of tree and shear parallel to grain did not vary in analyzed heights.…”
Section: Introductionmentioning
confidence: 99%
“…Many publications describe the various longitudinal variation patterns within trees. The recent work of Kiaei and Farsi (2016) for Persian silk wood (Albizzia julibrissin) illustrated wood density, modulus of elasticity and modulus of rupture in bending decreased from base to top with height, and Longui et al (2016) for Astronium graveolens showed specific gravity was higher at the base of tree and shear parallel to grain did not vary in analyzed heights.…”
Section: Introductionmentioning
confidence: 99%